2019
DOI: 10.1038/s41598-019-39497-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving lupeol production in yeast by recruiting pathway genes from different organisms

Abstract: Lupeol is a pentacyclic triterpene that shows a variety of pharmacological properties. Compared to engineering the production of sesquiterpenes and diterpenes, it is much more challenging to engineer the biosynthesis of triterpenes in microbial platforms. This study showed our efforts on engineering the triterpene pathway in Escherichia coli and Saccharomyces cerevisiae cells by recruiting the codon-optimized three lupeol pathway genes from different organisms. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…It suggests that gene expressions from the engineered squalene synthesis module and the MVA pathway do not impair cell growth of E. coli host, and their expression level is crucial to the improved squalene production. A peak titer of 272 mg/L was observed at culture of 48 hr, which was comparable to the achieved titer using squalene synthases of Homo sapiens and Thermosynechococcus elongatus (Katabami et al, 2015; Qiao et al, 2019). It suggested that these employed squalene synthases probably possess a similar capability to synthesize squalene.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…It suggests that gene expressions from the engineered squalene synthesis module and the MVA pathway do not impair cell growth of E. coli host, and their expression level is crucial to the improved squalene production. A peak titer of 272 mg/L was observed at culture of 48 hr, which was comparable to the achieved titer using squalene synthases of Homo sapiens and Thermosynechococcus elongatus (Katabami et al, 2015; Qiao et al, 2019). It suggested that these employed squalene synthases probably possess a similar capability to synthesize squalene.…”
Section: Resultssupporting
confidence: 65%
“…(Figure 1a) As squalene synthase catalyzes this abrupt transition from water‐soluble FPP to highly insoluble squalene, it generally anchors to the membrane by C‐terminal tail and exposes its catalytic domain to the cytosol (D. Zhang, Jennings, Robinson, & Poulter, 1993). Membrane‐anchored squalene synthases were thus truncated to improve solubilization for squalene production (Katabami et al, 2015; Qiao et al, 2019). A truncated S. cerevisiae squalene synthase gene erg 9 ( erg 9 TC ) was designed (Figure S1) and tandemly coupled to E. coli FPP synthase gene ispA to construct the squalene synthesis module IspA‐Erg9 TC (pTispAErg9 TC ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Introducing Lotus japonicus oxidosqualene cyclase and Medicago truncatula cytochrome P450 along with its native reductase enabled the production of betulin ( 8 ) and its precursor lupeol ( 9 ). In 2019, Qiao et al [ 118 ] presented biosynthetic production of lupeol ( 9 ) in Escherichia coli and Saccharomyces cerevisiae cells by recruiting three optimized lupeol pathway genes from different organisms. The authors introduced squalene synthase from Thermosynechococcus elongates , squalene epoxidase from Rattus norvegicus and lupeol synthase from Olea europaea into E. coli BL21(DE3).…”
Section: Biocatalyzed Production Of Lupane Triterpenoids—betulinic Acid (5) Betulin (8) and Lupeol (9)mentioning
confidence: 99%